Effect of Chelated Mineral Mixture on Blood Biochemistry, Hormone and Mineral Status in Repeat Breeder Buffaloes in Tribal Areas of Dahod District in Gujarat, India - Joshi, PM; Patel, DC; Patel, PD (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
An on-farm trial for 90 days was conducted at four tribal villages to assess the effect of chelated mineral mixture (CMM) supplementation on blood biochemistry as well as hormonal and mineral status, nutrient intake and reproductive performance of the repeat breeder buffaloes (n = 24). The animals selected were randomly divided into two groups of 12 animals each. The group T1 was control group (farmer’s feeding schedule), and T2 treatment group (T1 + CMM @ 50 g/animal/day). Blood collection was done at 0, 45 and 90 days of the experiment from both the groups for assessment of blood biochemical, hormonal and mineral status of the animals. Average DM, DCP and TDN intake in repeat breeder buffaloes calculated as per information collected from farmers were statistically similar among both the groups and were as per ICAR requirements of animals. Results revealed significant (p <0.05) improvement in hemoglobin, serum glucose, total protein, total cholesterol, progesterone, and macro (Ca, P)–micro (Zn, Fe, Cu, Co, Mn) mineral status of chelated mineral supplemented group as compared to control animals. The number of days taken for a successful conception in repeat breeder buffaloes as well as the cost of feeding was also reduced upon supplementation of CMM in T2 as compared to T1 group. The control group recorded a 22.12% higher cost of rearing than the treatment group during the experimental period. The findings revealed the beneficial role of cheated minerals supplementation in improving health, nutritional and reproductive status of repeat breeding buffaloes